Science for the sustainable city : empirical insights from the Baltimore School of Urban Ecology - Pickett, Steward T., 1950- (Yale University Press, 2019)
A presentation of key findings and insights from over two decades of research, education, and community engagement in the acclaimed Baltimore Ecosystem Study. In a world of over seven billion people-who mostly reside in cities and their suburbs and exurbs-the Baltimore Ecosystem Study is recognized as a pioneering program for modern urban social-ecological science, critical to the emerging theory of urban ecology. After two decades of research, education, and community engagement in this complex system, there are insights to share, generalizations to examine, and gaps to highlight. This timely volume synthesizes the key empirical findings, melds the perspectives of different disciplines, and celebrates the accomplishments of interacting with diverse communities and institutions in improving the understanding of Baltimore's ecology. These widely applicable insights from Baltimore contribute to our understanding the ecology of other cities, provide a comparison for the global process of urbanization, and inform establishment of urban ecological research elsewhere. Comprehensive, interdisciplinary, and highly original, it gives voice to the wide array of specialists who have contributed to this living urban laboratory.